Meeting housing needs of first-time homebuyers in Chinese cities - Tan, Teck-Hong * (2011)
The rate of homeownership in Chinese cities increased from less than 20% in the 1980s to 82% in 2007. However, such a high rate mainly resulted from the welfare housing policy which was abolished in 1998. In recent years, it has become much more difficult to become a homeowner in China, particularly first-time homebuyers who do not qualify for public rental housing units or afford private houses for self-use in urban areas. The sharp hike in housing prices in the past few years in Chinese cities have made homeownership a great challenge to most first-time homebuyers to own their home. The housing need for first-time homebuyers will continue to increase because it is the time that young households who are born after the 1980s have started to form their own families. The purpose of this paper is to discuss the challenges of promoting homeownership among young urban first-time homebuyers. This paper also offers suggestions regarding sustainable housing provision for them.